Influence of Work-Life Balance and Salary on Job Hopping Intention Among Generation Z Employees in the F&B Sector in Surabaya - Septian Dwiki Darmawan; K. Kustini (Manunggal Halim Jaya, 2026)
This study aims to examine the influence of work-life balance and salary on job hopping intention among Generation Z employees in the food and beverage (F&B) sector in Surabaya. A quantitative approach was employed using purposive sampling, involving 72 Generation Z employees working in the F&B sector in Surabaya. Data were collected through structured questionnaires and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS software. The findings reveal that work-life balance has a significant negative effect on job hopping intention (β = -0.575, p < 0.001), indicating that employees who experience a better balance between work and personal life are less likely to intend to leave their jobs. Likewise, salary has a significant negative effect on job hopping intention (β = -0.383, p < 0.001), suggesting that fair and adequate compensation reduces employees' intention to seek employment elsewhere. These findings highlight the importance of promoting work-life balance and implementing fair compensation practices as strategic human resource management initiatives to strengthen employee retention and reduce job hopping intention among Generation Z employees in the rapidly growing F&B industry.